Model of Guidance: Effective Communication with the Elderly for Empowering Elderly Caregivers in Nursing Homes in Indonesia - Minarti Minarti; Siti Nur Kholifah; Heru Sulistijono; Hilmi Yumni; Y.K Windi; Asnani Asnani; Intim Cahyono; Hasyim As’ari; Bambang Heriyanto; Nikmatul Fadilah; Dyah Wijayanti; Suriana Suriana; Baiq Dewi Harnani; Dinarwiyata Dinarwiyata; Eko Rustamaji W; Ferry Kumala (Frontiers in Community Service and Empowerment, 2022)
Activities related to increasing the caregiver's ability to care for the elderly who experience daily problems related to psychological approaches and the like have never been carried out. Caregiver communication does not support effective communication and is still social communication. Supported by the results of research conducted at the Nursing Home for the Elderly, it showed that there was a difference between pre and post-test in the group that received guidance or counseling treatment on the happiness of the elderly with a significant value. The purpose of this training is to empower elderly caregivers at Nursing Home at St. Yosef, Surabaya, and identify the effectiveness of the guidance model (Guidance) by caregivers. The number of participants is 50 people. The method used is cadre training through discussions, demonstrations, competence training and competence assessment. The result of training for caregivers is an increase in knowledge based on pre-test and post-test scores. There was an increase in skills seen in four skills, namely communication in the elderly, active movement, passive movement, mobilization, and daily activity training. The advantage of this cadre training is that it can effectively improve communication with the elderly people who are cared for in the orphanage. The implication of this activity is to increase the knowledge and skills of caregivers in providing care for the elderly through effective communication with the elderly in nursing homes as an effort to improve the health of the elderly.